2005
DOI: 10.20886/ijfr.2005.2.1.27-36
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Changes of Kekabu Wood (Bombax ceiba L.) Due to Mechanical Densification

Abstract: Kekabu is a trade name of Bombax ceiba L. wood, which is popularly known as kapok or randu wood. It is formerly named Gossampinus malabarica DC. Merr. and belongs to family Bombacaceae. In some area kekabu wood is mixed in consignments that are mainly comprising wood of Durio spp. and traded as 'durian wood'. Kekabu's heartwood is not clearly demarcated with its white yellowish sapwood. Wood texture is smooth and even, so that clean yellowish kekabu wood appearance is potentially developed as luxury timber. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
0
5
0
1
Order By: Relevance
“…Densification on light coconut wood is similar to that of studying carried out on less dense conventional wood. Krisdianto and Balfas (2005) reported that anatomical changes of Kekabu (Bombax ceiba L.) wood, which was caused by steam-pressure densification, reduced void volume and improved density of light Kekabu wood. The anatomical changes of Kekabu wood depend on grain orientation of the wood samples.…”
Section: Resultsmentioning
confidence: 99%
“…Densification on light coconut wood is similar to that of studying carried out on less dense conventional wood. Krisdianto and Balfas (2005) reported that anatomical changes of Kekabu (Bombax ceiba L.) wood, which was caused by steam-pressure densification, reduced void volume and improved density of light Kekabu wood. The anatomical changes of Kekabu wood depend on grain orientation of the wood samples.…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 shows the average increase values of the two different woods after the densification processes. The values found in the available literature are in the range of +25% and +135% [13,15,16]. During the delignification and densification processes, the wood sample colors increasingly turned towards darker shades.…”
Section: Wood Densificationmentioning
confidence: 95%
“…Observing the material from the external side of the specimen, it is almost impossible to notice the presence of fibers even at higher magnifications. This homogenous conformation is provided by the collapse of the cellular structure [15,16]. SEM images of all samples after densification process are reported in Figure 4.…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of wood densification mainly depends on treatment conditions, the wood species, and initial treatment, all of which can be modified (Wahyudi, 2013). Densification has been reported to be suitable for fast-growing species such as Agathis alba (Sulistyono et al, 2003), Ceiba pentandra (Krisdianto and Balfas, 2005), Cocos nucifera (Krisdianto, 2006), Enterolobium cyclocarpum, Maesopsis eminii, and Durio sp. (Ratih et al, 2009), as well monocotyl such as oil palm (Hartono et al, 2016).…”
Section: Introductionmentioning
confidence: 99%